Answers

2014-12-10T19:10:25+05:30


3x + 2y = 4 ....... Equation (1)

2x - y    = 5  .......Equation (2)

Multiplying the equation (2) by 2, we get,

4x - 2y   = 10 .....Equation (3)

Adding equation (1) and (3),

              3x + 2y = 4

           + 4x - 2y  = 10

         _______________

              7x         = 14

                x         = 2

Therefore, substituting x = 2 in equation (2), we get,

       2(2) - y = 5

       4     - 5  = y

            y      = -1

Therefore, solution set = { 2, -1 }

0